If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 105 + 9.50x = 14.75x + 105 Reorder the terms: 105 + 9.50x = 105 + 14.75x Add '-105' to each side of the equation. 105 + -105 + 9.50x = 105 + -105 + 14.75x Combine like terms: 105 + -105 = 0 0 + 9.50x = 105 + -105 + 14.75x 9.50x = 105 + -105 + 14.75x Combine like terms: 105 + -105 = 0 9.50x = 0 + 14.75x 9.50x = 14.75x Solving 9.50x = 14.75x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14.75x' to each side of the equation. 9.50x + -14.75x = 14.75x + -14.75x Combine like terms: 9.50x + -14.75x = -5.25x -5.25x = 14.75x + -14.75x Combine like terms: 14.75x + -14.75x = 0.00 -5.25x = 0.00 Divide each side by '-5.25'. x = 0 Simplifying x = 0
| 2r-3=-3-7r | | -6x^2+23= | | 3(5p-3)=5(p+7) | | 3(5p-3)=5(p+7) | | 12+(7+3)2= | | -6x^2+23= | | 12+(7+3)2= | | 4m+17=-(4-m) | | 5.5=-2 | | h(t)=30t-2t^3 | | w+6=6(w-6) | | 12+(7+32)= | | 9/11/9= | | -4(x+3)=36 | | 7z=72 | | 5x-10/6x-6 | | 10x/12=-28 | | 24n+18=4n-2 | | 7/3x=77/4 | | 4j+6j=8.6 | | -4s-5+6-3s= | | -9-2x=17-x | | 3x+27=4.5x | | 90=(x+2)(5x) | | Y=-.25x+1 | | -37=12+-85 | | DX(t)/dt | | 12x-93=3x+105 | | (X^2)-((y^2)/35)=1 | | 0.33(x-16)=-2(x-3)+4 | | 2(3x-2)-2=2(x-2)+6 | | -8(3x+1)=8x-7(6x+5) |